2017
DOI: 10.1111/odi.12648
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the combination of tyrosol with chlorhexidine gluconate on oral biofilms

Abstract: The combination of tyrosol with chlorhexidine gluconate was only effective in reducing the number of hyphae by C. albicans, a relevant virulence factor of this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…Arias et al (2016) showed that tyrosol treatment at concentrations ranging from 100 to 200 mM exerted a significant reduction in metabolic activity against C. albicans and C. glabrata two-day-old oral biofilms, which was proportional to a reduction in cell number [ 103 ]. Do Vale et al (2017) showed that tyrosol alone at concentrations of 50 and 90 mM demonstrated inhibition of the planktonic growth of C. albicans and C. glabrata cells, respectively [ 104 ]. However, tyrosol does not significantly reduce metabolic activity or the number of cells for one-day-old oral biofilms; in addition, the nature of interaction of tyrosol with chlorohexidine gluconate was indifferent.…”
Section: Tyrosolmentioning
confidence: 99%
See 1 more Smart Citation
“…Arias et al (2016) showed that tyrosol treatment at concentrations ranging from 100 to 200 mM exerted a significant reduction in metabolic activity against C. albicans and C. glabrata two-day-old oral biofilms, which was proportional to a reduction in cell number [ 103 ]. Do Vale et al (2017) showed that tyrosol alone at concentrations of 50 and 90 mM demonstrated inhibition of the planktonic growth of C. albicans and C. glabrata cells, respectively [ 104 ]. However, tyrosol does not significantly reduce metabolic activity or the number of cells for one-day-old oral biofilms; in addition, the nature of interaction of tyrosol with chlorohexidine gluconate was indifferent.…”
Section: Tyrosolmentioning
confidence: 99%
“…However, tyrosol does not significantly reduce metabolic activity or the number of cells for one-day-old oral biofilms; in addition, the nature of interaction of tyrosol with chlorohexidine gluconate was indifferent. Nevertheless, 1.25 mM tyrosol with 0.00725 mM chlorhexidine gluconate showed a synergistic interaction in reducing the number of hyphae formed [ 104 ]. A combination of tyrosol and farnesol has been explored for oral Candida isolates for both planktonic and sessile growth.…”
Section: Tyrosolmentioning
confidence: 99%
“…Because implants need a rough surface for osseointegration, the use of mechanical measures, such as periodontal scaling [10], dental floss, or rinsing may not be a feasible option [11]. Chemical plaque control, such as the use of chlorhexidine mouthwashes, has an effective role in controlling microorganisms including Streptococcus mutans [12] and Candida albicans [13] and periodontal pathogens such as P. gingivalis and Aggregatibacter actinomycetemcomitans [14]. Although chlorhexidine has an effective action against oral bacteria, its long-term use can lead to unwanted effects, such as altered sensations in taste, discoloration of the oral mucosa/tongue/gingiva [15], imbalances of the oral flora, and the development of drug resistance [16].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorhexidine at low concentrations, but with the addition of cis-2-decenoic acid, was able to disperse single-species biofilms formed by S. mutans and C. albicans, as well as bacterial-fungal dual-species consortia [56]. Also, chlorhexidine gluconate with tyrosol was revealed to be effective against single and mixed-species oral biofilms [57,58]. A solution containing 2.5% sodium hypochlorite, 2% chlorhexidine, and ozonated water inhibited biofilms of S. mutans and C. albicans in mesiobuccal root canals after irrigation [25].…”
Section: Chemical Compounds With Activity Against Streptococcus Mutanmentioning
confidence: 99%